Instructional test bench for marine purpose diesel piston engines - Petrescu, Valentin; Savescu, Claudia; Contiu, Rares; Tomescu, Sorin; Nechifor, Cristian; Serban, Alexandru; Isac, Robert (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The paper presents the development of an instructional test bench designed to support the training of marine cadets in the operation and maintenance of tugboat propulsion systems powered by diesel engines. The test bench, developed by the authors and implemented at the Naval Academy “Mircea cel Bătrân” in Constant,a, Romania, is intended to enhance practical understanding of propulsion system components and operating principles. The installation enables instruction on the construction and operation of four-stroke internal combustion engines, as well as on the correct monitoring of key parameters associated with a marine diesel engine, reversing gearbox, and hydraulic brake. Successive loading of the engine can be performed, allowing the analysis of engine behavior and power development under controlled operating conditions. The test bench comprises a diesel engine, reversing gearbox, axial shaft, and a downsized hydraulic brake coupled through a multiplier gearbox for emulating the propeller load. A custom-designed automation and control system is implemented, providing local and remote command consoles together with a replicating display for parameter monitoring. Auxiliary systems include compressed air supply, fuel storage and delivery, exhaust gas evacuation, cooling, and lubrication systems for both the engine and the brake.